Sistem Deteksi Dan Perhitungan Otomatis Bakteri Salmonella dengan Pengolahan Citra Menggunakan Metode Object Counting - Lashot Ria Ingrid Melanika; Hurriyatul Fitriyah; Gembong Edhi Setiawan (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2018)
Salmonella is one of the pathogenic bacteria that can cause disease in human digestive tract. The microscopic size makes the Salmonella bacteria invisible without the aid of a microscope. Detection and calculation of bacterial colonies during microscopic observations are still done manually until now. Therefore designed a system that can detect and perform calculations on Salmonella bacteria colonies automatically using the method of color segmentation and object counting. Samples of Salmonella bacteria isolated from chicken meat were made on glass preparations and gram staining was done to make it easier to observe. Bacteria shooting is using the camera on a digital microscope with a resolution of 5 mega pixels. The first process in image processing is image enhancement, then converting RGB image to HSV image. After that performed closing morphological operation, then bacterial colonies were calculated by object counting method. The processing of image processing algorithms is performed on MATLAB, and the system will be displayed on an interface to make it easier for user. The accuracy of input and image information to obtain results with successful status. The average time required during the execution of the system is 4.59 seconds, and the accuracy of detection and calculation of the number of bacterial colonies has an accuracy by 80.81%.